2009
DOI: 10.1088/0029-5515/49/12/125008
|View full text |Cite
|
Sign up to set email alerts
|

Mirror stabilization experiments in the Hanbit device

Abstract: The Hanbit magnetic mirror device has been involved in a series of experiments on stabilization of the MHD flute type mode. We undertook investigations to see whether a divertor and the kinetic stabilizer (KS) of Post et al can stabilize the MHD instability. The Hanbit divertor configuration used one of the central cell coils with reversed current as the divertor coil and two other coils with increased current to compensate the field droop. The divertor eliminated the m = −1 instability when the null point was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…[22][23][24] The experiments realize the steady state operation where the plasma radial loss is balanced with the plasma production. The flute modes can be stabilized by the divertor as mentioned in Sec.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] The experiments realize the steady state operation where the plasma radial loss is balanced with the plasma production. The flute modes can be stabilized by the divertor as mentioned in Sec.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] It was reported that the flute modes were stabilized by the divertor mirror experimentally. [22][23][24] Because the classical radial transport is large around x-point, the diffusion forms locally stable pressure profile ͑with ‫ץ‬U / ‫ץ‬ ͒ in the neighborhood of magnetic null and unstable pressure profile outside this area and so ‫ץ‬pU ␥ / ‫ץ‬ =0 is not satisfied around the separatrix ͑i.e., around the plasma boundary͒, which can destabilize the flute modes. The quantity relates to the magnetic flux defined by B = ٌ ϫ ٌ , where ͑ , , ᐉ͒ coordinates are used.…”
Section: Flute Stabilitymentioning
confidence: 99%
“…26 The experimental studies were also carried out by the tandem mirrors. [27][28][29] In the following the MHD stability mechanism by a magnetic divertor is mentioned briefly. The magnetic divertor has a magnetic null at the separatrix in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Modern axially symmetric magnetic mirror traps are among the simplest magnetic plasma confinement devices in addition to their intrinsic capability of steady-state operation. In recent years substantial progress in the suppression of longitudinal heat losses to the end walls via electron thermal conductivity [12], in the stabilization of plasma MHD instabilities [13,14] and in the understanding of key physical phenomena determining plasma confinement and heating [15] in mirror systems have contributed to laying the foundation for their fusion reactor relevance.…”
Section: Progress On Mirror Experimentsmentioning
confidence: 99%